Dermatomyositis and/or polymyositis as a paraneoplastic manifestation of ovarian cancer: a systematic review - Psomiadou, Victoria; Gkegkes, Ioannis D.; Iavazzo, Christos (Contemporary Oncology/Współczesna Onkologia, 2020)
Dermatomyositis (DM) is defined as an autoimmune inflammatory disease that affects the skin, the blood vessels and the muscles. It typically presents with erythema affecting mostly the eyes and the hands as well as proximal muscle weakness. It has been also correlated with various types of cancer, including ovarian cancer. A systematic PubMed and Scopus search was conducted. A total of 110 women were included in our review. The median age of the patients was 52.5 years (8–85). The most frequent histological type of malignancy was epithelial (87 cases, 79.1%) and in only one patient (0.9%) DM was co-existing with a cancer recurrence. A clinical diagnosis of DM or PM preceded the diagnosis of ovarian cancer in 69.1% (76/110), while paraneoplastic DM after the diagnosis of ovarian cancer was reported in 31% (34/110). Serum antibodies were present in 22.5% (25/110) and the median creatine kinase during first evaluation was 886 (56.6–16,596). Postoperative improvement of the symptoms was observed in 24.6% (27/110) while also 24.6% (27/110) needed post-treatment rheumatological management. Neoadjuvant chemotherapy or radiotherapy was necessary in 58.2% (64/110) and a cancer recurrence was identified in 28.2% (31/110), with a median follow up of 24.5 months (5–210). Finally, 52 (47.3%) deaths were reported in a median follow-up period of 16 months (0–210). It is crucial that DM patients should receive a thorough evaluation for ovarian cancer, among other malignancies, encompassing an abdominal CT or MRI scan and serum Ca-125 marker measurements. Treatment of ovarian cancer is usually accompanied by remission of DM symptoms in most of the cases.